Human capital and development : lessons and insights from Korea's transformation - Yi, Chu-ho, 1961-; Jeong, Hyeok; Hong, Seong-Chang; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
Over the last 70 years, Korea has experienced a rapid and remarkable transformation from a devastatingly poor nation to one of the world's leading advanced economies, achieving both sustained economic growth and a successful democracy. This pioneering work focuses on the key role of sustained investment in human capital behind Korea's phenomenal success. Human Capital and Development analyzes the importance of balancing diverse aspects of the educational system at different stages of development. The need to balance general and vocational education, top-down and bottom-up reform, as well as qualitative and quantitative expansion are highlighted. Adapting Korea's development experience to general principles shows that rather than seeking universal strategies and rules, the key to successful transformation is the provision of educational systems that can evolve over time depending on socio-economic and technological conditions for both developing and advanced countries. For researchers and students of economic development, education, and Asian development, this book is an excellent tool to discover possible ways for developing countries to initiate and accelerate their paths of economic growth and development. This book also provides a useful reference for policy makers of advanced as well as developing countries in designing their education systems and policies.
Contents: Foreword -- Introduction -- 1. Accumulating human capital for sustainable development -- 2. Education bubble and widening inequality -- 3. Making education diversification reform happen -- 4. Turning around failing vocational high schools -- 5. Deteriorating skills and weak life-long learning -- 6. Fostering project-based learning and performance assessment -- 7. Stimulating high-risk high-payoff research -- 8. Nuts and bolts of the aid for TVET -- Reference -- Index.
Includes bibliographical references and index.
Description based on print record.
Keywords: Human capital -- Korea; Economic development -- Korea; Electronic books